Pemanfaatan Kain Flanel sebagai Aneka Kerajinan Tangan untuk Menumbuhkan Jiwa Kewirausahaan bagi Remaja Putus Sekolah di Desa Permata, Boalemo - Lanto Miriatin Amali; Melizubaida Mahmud (Universitas Mathla'ul Anwar Banten, 2019)
UTILIZATION OF FLANNEL AS HANDICRAFTS TO GROW ENTREPRENEURSHIP FOR SCHOOL DROPOUTS IN PERMATA VILLAGE, BOALEMO. The devotion program aims to empower teenagers who drop out of school in the gem village of Paguyaman district in Boalemo district through the use of flannel fabrics while fostering an entrepreneurial spirit. The proposal and method of solving problems in this Community Service program is to train teenagers who drop out of school to make various kinds of handicrafts from flannel, develop this flannel fabric motif in accordance with the characteristics of Permata Village, and develop marketing distribution especially in Boalemo district. The partner in this service Ranti Taylor with the owner's name is Abas Aminah whose business is convection and the only one is in Permata Village. This can make it easier for teenagers to drop out of school to conduct training while developing handicrafts from flannel fabrics from various motives while creating new designs so that they are more skilled in making them.